1997
DOI: 10.1080/07315724.1997.10718664
|View full text |Cite
|
Sign up to set email alerts
|

Postexercise energy expenditure and substrate oxidation in young women resulting from exercise bouts of different intensity.

Abstract: These data indicate that the recovery period should also be considered when determining the impact of different exercise intensities on total energy expenditure and fat and carbohydrate utilization in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
1
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 13 publications
4
48
1
5
Order By: Relevance
“…32 Exercise not only increases total energy expenditure due to the extra energy expended during the exercise but also due to an elevated postexercise energy expenditure. Some studies have shown that HI exercise has a more pronounced effect on postexercise energy expenditure compared to LI exercise, [13][14][15] whereas other found no difference. 16,17 However, these studies only measured energy expenditure for several hours after the exercise bout.…”
Section: Discussionmentioning
confidence: 99%
“…32 Exercise not only increases total energy expenditure due to the extra energy expended during the exercise but also due to an elevated postexercise energy expenditure. Some studies have shown that HI exercise has a more pronounced effect on postexercise energy expenditure compared to LI exercise, [13][14][15] whereas other found no difference. 16,17 However, these studies only measured energy expenditure for several hours after the exercise bout.…”
Section: Discussionmentioning
confidence: 99%
“…Others report an extended increase in postexercise energy expenditure after just 20 min of cycling at 70% maximum aerobic capacity (3), and differences between studies may be related to control of subject energy intake and daily activities. Several investigators emphasize that elevations in postexercise energy expenditure depend on the degree of homeostatic disturbance and that RMR is elevated especially after high-intensity long-duration exercise (6,23). For example, rates for postexercise energy expenditure were elevated for 0.3, 3.3, and 10.5 h in six males cycling for 80 min at 29%, 50%, and 75% of maximum aerobic capacity (4).…”
mentioning
confidence: 99%
“…Alguns autores têm reportado que o gasto energético após um exercício de alta intensidade é superior ao observado em outro de baixa intensidade 2,3 . Tem sido relatado também que, além de levarem ao aumento do consumo de oxigênio, os exercícios de alta intensidade favorecem o aumento da oxidação de gordura, efeito este benéfico para o controle de peso e do teor de gordura corporal 4 .…”
Section: N T R O D U ç ã Ounclassified